Security as emancipation: A theoretical reconsideration - Terrenas, J. (2021)
This thesis sets out to reconsider security as emancipation. Security as emancipation is a theoretical framework for the critical analysis, normative assessment, and political reconsideration of existing security arrangements, grounded upon the struggles and insecurities of real people in real places. However, in its current formulation, this theory still has some insufficiencies that reduce its analytical, normative, and transformative potential. This thesis seeks to tackle this issue. Drawing upon the method of immanent critique, it investigates how the theoretical framework of security as emancipation can be strengthened by incorporating critical resources from the ethnographic, practice, and posthuman turns in social and political thinking. The thesis puts forward four arguments. First, integrating ethnographic methods into this theory will make it better prepared to engage with the struggles and insecurities of real people in real places. Second, incorporating critical resources from practice thinking can enable security as emancipation to better assess the social construction of existing security arrangements and their implications upon real people in real places. Third, engaging posthuman thinking can allow security as emancipation to reconsider the ethical, political, and affective relation between the insecurity of real people and the security of real places. Finally, once equipped with critical resources from these turns, the theory of security as emancipation can create new openings in the agenda of critical security studies. The argument offers a contribution to extant discussions in critical security studies by illuminating some of the benefits that can result from exploring the potential synergies between critical security theories and critical security turns.